2020
DOI: 10.3390/polym13010029
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Biosafety Analysis of Resorbable Polyglycolic Acid-Polylactic Acid Block Copolymer Composites for Spinal Fixation

Abstract: Herein, spinal fixation implants were constructed using degradable polymeric materials such as PGA–PLA block copolymers (poly(glycolic acid-b-lactic acid)). These materials were reinforced by blending with HA-g-PLA (hydroxyapatite-graft-poly lactic acid) and PGA fiber before being tested to confirm its biocompatibility via in vitro (MTT assay) and in vivo animal experiments (i.e., skin sensitization, intradermal intracutaneous reaction, and in vivo degradation tests). Every specimen exhibited suitable biocompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…As a material with a relatively slow degradation rate, PLLA may cause some problems, such as incomplete degradation and lower local pH. Therefore, PLLA implants may cause late inflammation, cell necrosis, and delayed axonal recovery in the body [91], which should also be considered for future clinical applications.…”
Section: Topography Affects Cell Alignment Growth and Neuritementioning
confidence: 99%
“…As a material with a relatively slow degradation rate, PLLA may cause some problems, such as incomplete degradation and lower local pH. Therefore, PLLA implants may cause late inflammation, cell necrosis, and delayed axonal recovery in the body [91], which should also be considered for future clinical applications.…”
Section: Topography Affects Cell Alignment Growth and Neuritementioning
confidence: 99%
“…Later, synthetic polymer-based fluid loss agents evolved as a kind of natural material modification, improving the temperature resistance. Graft copolymerization was used to alter starch using monomers such as acrylamide, acrylic acid, 2-acrylamido-2-methylpropane sulfonic acid, and dimethyldiallylammonium chloride. While the environmental acceptability quality of these starch graft copolymers looks to be sufficient and meets the ever-increasing environmental standards, the method by which these composites were created is unknown. To guarantee efficient and secure drilling, it is crucial to create high-temperature-resistant fluid loss agents for drilling fluids. Moreover, ion exchange processes are anticipated in high-salinity formations where the salt concentration in the drilling fluid is similar to the salt concentration in the formation, resulting in drilling fluid instability.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable aliphatic polyesters such as PCL and PLA, endowed with semicrystallinity and biodegradability due to their potentially hydrolyzable ester bonds, have been widely used as scaffolds in tissue engineering, drug delivery systems, packaging, and biomedical applications, because of their controlled biodegradability, biocompatibility, and good physical properties [1][2][3]. It has been reported that, compared to PLA, the degradation period of PCL can range from several months to a few years, and its biodegradability is dependent on its molecular weight, degree of crystallinity, and degradation conditions.…”
Section: Introductionmentioning
confidence: 99%